2013
DOI: 10.1159/000348763
|View full text |Cite
|
Sign up to set email alerts
|

Primary Intestinal Lymphangiectasia: Is It Always Bad Two Cases with Different Outcome

Abstract: Primary intestinal lymphangiectasia (PIL) or Waldmann's disease is a rare protein-losing gastroenteropathy of unknown etiology. Less than 200 cases have been reported globally. Patients may be asymptomatic or present edema, lymphedema, diarrhea, ascites and other manifestations. We report two pediatric cases with PIL with extremely different outcome in a 3-year follow-up period. The first patient presented with persistent diarrhea, hypoalbuminemia and failure to thrive, while the second patient presented with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 27 publications
2
28
0
Order By: Relevance
“…Some patients have a short period of fever initially, while others present with acute ileus and some develop the symptoms gradually [2,4,5,[8][9][10][11][12][13][14][15] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some patients have a short period of fever initially, while others present with acute ileus and some develop the symptoms gradually [2,4,5,[8][9][10][11][12][13][14][15] .…”
Section: Discussionmentioning
confidence: 99%
“…IL was first described in 1961 by Waldmann et al and since then about 200 cases have been reported [1,[4][5][6][7] . We present a patient with primary IL as a rare cause of intractable, but potential curable ascites.…”
Section: Introductionmentioning
confidence: 99%
“…Primary intestinal lymphangiectasia is usually diagnosed in childhood, but adult cases have also been reported. Worldwide, few over 200 cases have been described [3]. The diagnosis is confirmed by the endoscopic appearance of the small bowel lymphangiectasia and the corresponding histology on the biopsies.…”
Section: Introductionmentioning
confidence: 90%
“…The histopathology report of the enterobiopsy specimens confirmed the diagnosis of PIL (Figs. 3,4). Immunohistochemistry was negative for lymphoma.…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation